Pacific-Ciguatoxin-2 and Brevetoxin-1 Induce the Sensitization of Sensory Receptors Mediating Pain and Pruritus in Sensory Neurons - Pierre, Ophélie (Mar Drugs, 2021)
Ciguatera fish poisoning (CFP) and neurotoxic shellfish poisoning syndromes are induced by the consumption of seafood contaminated by ciguatoxins and brevetoxins. Both toxins cause sensory symptoms such as paresthesia, cold dysesthesia and painful disorders. An intense pruritus, which may become chronic, occurs also in CFP. No curative treatment is available and the pathophysiology is not fully elucidated. Here we conducted single-cell calcium video-imaging experiments in sensory neurons from newborn rats to study in vitro the ability of Pacific-ciguatoxin-2 (P-CTX-2) and brevetoxin-1 (PbTx-1) to sensitize receptors and ion channels, (i.e., to increase the percentage of responding cells and/or the response amplitude to their pharmacological agonists). In addition, we studied the neurotrophin release in sensory neurons co-cultured with keratinocytes after exposure to P-CTX-2. Our results show that P-CTX-2 induced the sensitization of TRPA1, TRPV4, PAR2, MrgprC, MrgprA and TTX-r NaV channels in sensory neurons. P-CTX-2 increased the release of nerve growth factor and brain-derived neurotrophic factor in the co-culture supernatant, suggesting that those neurotrophins could contribute to the sensitization of the aforementioned receptors and channels. Our results suggest the potential role of sensitization of sensory receptors/ion channels in the induction or persistence of sensory disturbances in CFP syndrome.